Desdobramento do planejamento estrategico: desenho de metodologia estruturada para uma organização hospitalar - Julia Schneider Ataide Assis (2024)
Healthcare organizations in Brazil are experiencing a challenging scenario in terms of growth, profitability and increase customer base, pressured by concentration of large vertical players, rised prices from suppliers and discounts requests from service buyers. Strategic planning has been identified as a differentiator for organization success, however, it is not easily converted into a support decision-making tool, requiring it to be properly structured and incorporated into the organizational culture. The adoption of a systematized and collaborative structure to clearly define objectives and means to arise them has proven to be the path to differentiation and achievement of the strategy. The objective of this research was to design a methodology for strategic planning deployment in a hospital organization. This research was a methodological single study case, with a qualitative approach that studied manager’s experience with strategic planning in a healthcare organization. The data collection technique involved semi-structured interviews with managers of a healthcare organization. A integrative literature review preceded the field research and was carried out through a search for publications, covering the period from 2013 to 2022, in the following databases: BVS Regional Portal, Medline via PubMed, Scopus, Cochrane and Embase. The descriptors used was Strategic Planning, Strategic Objectives and Hospitals, and synonymous keywords, in Portuguese, English and Spanish. Field research data analysis used the content analysis technique, specifically, thematic analysis. The categories were defined a posteriori based on the critical analysis of the manual interviews transcription. The research brought as results the association of literature with the experience of organization's managers interviewed, in sumary (1) the importance of senior leadership as a sponsor, director and disseminator of strategic planning for a greater chance of success in its execution, (2) the mission of leadership as a link in this process to disseminate information and engage the team in fulfilling its role to the strategy, (3) the need to unfold the strategy in a transparent and cohesive way, involving the largest number of stakeholders, in smaller blocks and in language accessible to employees, (4) the function of periodic monitoring as support to strategy development and to stimulate the achievement of results and review of actions in case of non-compliance with them, (5) the engagement and participation of employees as essential for the success of the plan, and (6) the existence of a financial bonus linked to strategic planning process as a potential motivational factor for the team.The products of this research included: the design of a structured methodology for deploying strategic planning for the organization setting this study and the elaboration of a methodology implementation project, with definition of steps, people involved, indicator selection model, monitoring process, tools for creating action plans and framework for formalizing individual goals. It is suggested for future studies a research in the organization to elucidate the knowledge and experience of managers in the implementation of the strategic planning process, covering a greater number of interviewees, as well as the quantitative evaluation of the results obtained by the organization with the strategic planning implementation following the steps defined by the chosen methodology.